2017
DOI: 10.3390/molecules22101752
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Evaluations of 1,3,5-Triazine Derivatives of Metformin Cyclization with Berberine and Magnolol in the Presence of Sodium Methylate

Abstract: The novel target products were synthesized in the formation of a triazine ring from berberine, magnolol, and metformin catalyzed by sodium methylate. The structures of products 1–3 were firstly confirmed by extensive spectroscopic analyses and single-crystal X-ray diffraction. The crystal structures of the target product 2 and the intermediate product 7b were reported for the first time. All target products were evaluated for their anti-inflammatory and antidiabetic activities against INS-1 and RAW264.1 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…HFD combined with STZ injection is a common method to model obese T2DM. Excess weight gain, obesity, hyperglycemia, hyperlipidemia and insulin resistance are found in the model rats . In obese T2DM, abnormal lipid metabolism in WAT can cause lipid efflux, lipid deposition and adipose tissue inflammation, which is closely related to the occurrence and development of insulin resistance .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HFD combined with STZ injection is a common method to model obese T2DM. Excess weight gain, obesity, hyperglycemia, hyperlipidemia and insulin resistance are found in the model rats . In obese T2DM, abnormal lipid metabolism in WAT can cause lipid efflux, lipid deposition and adipose tissue inflammation, which is closely related to the occurrence and development of insulin resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Excess weight gain, obesity, hyperglycemia, hyperlipidemia and insulin resistance are found in the model rats. 28,29 In obese T2DM, abnormal lipid metabolism in WAT can cause lipid efflux, lipid deposition and adipose tissue inflammation, which is closely related to the occurrence and development of insulin resistance. 30 In the present study, BMH473 demonstrated a significant lower body weight, blood glucose and lipid content in obese T2DM rats (Table 1 and Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations